Correlation Between Parenting Styles and Behavioral Disorder on Children With Mental Retardation - Akmalia, Andi Rasyida; Febriyana, Nining; Suryawan, Ahmad; Khanfar, Sarah Amjad (Jurnal Psikiatri Surabaya, 2026)
Introductions: Mental retardation can be defined as a significant and direct lack of overall intellectual functioning that causes social maladaptation, a condition due to below-average intelligence. The lack of intellectual function will affect all levels of intelligence, including social behavior skills in society that cause a behavioral disorder. Mentally retarded children require appropriate parenting styles to prevent behavioral disorders. The aim of this study is to assess the relationship between parenting styles and behavioral disorders in children with mental retardation at the Child Psychiatry Daycare Unit of Dr. Soetomo Regional General Hospital Surabaya. Methods: This research is an observational study with a cross-sectional design using a quantitative approach. The research sample was taken from the study population who had met the inclusion and exclusion criteria so that 40 respondents were obtained. This study examines the relationship between two variables. The parenting variable was measured using the Kuesioner Pola Asuh Anak dan Remaja (KPAA), and the behavioral disorder variable in mentally retarded children was measured using the Abberant Behavior Checklist (ABC) Questionnaire. Results: Data were analyzed using the Spearman correlation test. The correlation coefficient was 0.635 with a significant value (p-value) < α 0.05. The findings demonstrated a strong and linear relationship between parenting styles and behavioral disorders in mentally retarded children. Conclusion: In conclusion, authoritative parenting tends to cause mild behavioral disorders in mentally retarded children, while authoritarian and permissive parenting tend to cause severe behavioral disorders in mentally retarded children.